Problematising the popular discourses about language and identity of young adults in Bangladesh - Shaila Sultana, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The prevailing discourses of the print media in Bangladesh critique the way younger generations use English in their everyday Bangla conversations and show an increased concern about the purity of the Bangla language. It is assumed that the younger generations are in the verge of destroying the sovereignty of Bangla with their indiscriminate insertion of English words in Bangla sentences. It is also presumed that the younger generations are subjugated by the colonial legacy of English and consumed by the Western culture, and hence, they fail to maintain the sanctity of Bangladeshi culture and identity. However, acknowledging the political, ideological, and hegemonic role of English and globalisation, this paper problematises these simplistic assumptions. It demonstrates that any view that represents English as a tool of colonisation and neocolonisation or younger generations as responsible for the ‘language pollution’, somewhat understates the underlying complexities in these discourses. Hence, the paper has two distinct focuses. First, the paper discusses the role of English as a language of colonisation and globalisation in the context of Bangladesh. Second, it analyses the historical, political, ideological, and socio-cultural significance of Bangla in relation to its different regional varieties and indigenous languages. Based on these discussions, the paper finally indicates that the younger generations deserve a deeper understanding of the multifaceted factors that influence their language practices and their locatedness within the local and global linguistic and cultural flows.